Interacting Bioenergetic and Stoichiometric Controls on Microbial Growth - Chakrawal, Arjun; Calabrese, Salvatore; Herrmann, Anke M.; Manzoni, Stefano (Frontiers in Microbiology, 2022)
Microorganisms function as open systems that exchange matter and energy with their surrounding environment. Even though mass (carbon and nutrients) and energy exchanges are tightly linked, there is a lack of integrated approaches that combine these fluxes and explore how they jointly impact microbial growth. Such links are essential to predicting how the growth rate of microorganisms varies, especially when the stoichiometry of carbon (C) and nitrogen (N) uptake is not balanced. Here, we present a theoretical framework to quantify microbial growth rate for conditions of C, N, and energy (co-)limitation. We use this framework to show how the C:N ratio and degree of reduction of organic matter (OM, also the electron donor), availability of electron acceptors, and different sources of N together control the microbial growth rate under C, nutrient, and energy-limited conditions. We show that growth rate peaks at intermediate values of the degree of reduction of OM under oxic and C limited conditions, but not under N limited conditions. Under oxic conditions and with N-poor OM, the growth rate is higher when the inorganic N source is ammonium compared to nitrate due to the additional energetic cost involved in nitrate reduction. Under anoxic conditions, when nitrate is both the electron acceptor and the inorganic N source, the growth rates of denitrifiers and microbes performing dissimilatory nitrate reduction to ammonia (DNRA) are determined by both OM degree of reduction and nitrate availability. Consistent with data, DNRA is predicted to foster growth under extreme nitrate limitation and reduced OM, whereas denitrifiers are favored as nitrate becomes more available and in the presence of oxidized OM. Furthermore, the growth rate is reduced when catabolism is coupled to low energy yielding electron acceptors (e.g., sulfate) because of low C use efficiency. However, low CUE also decreases nutrient demand for growth thereby reducing N limitation. We conclude that bioenergetics provides a useful conceptual framework for explaining growth rates under different metabolisms and multiple resource limitations.